Meal patterns of Malaysian adults: Findings from the Malaysian adults nutrition survey (MANS) - WM, Wan Abdul Manan; Isa, Nur Firdaus; Md. Yusof, Safiah; MD, Siti Haslinda; Poh, Beekoon; Abdul Karim, Norimah; MY, Azmi; Aris, Tahir; Kandiah, Mirnalini; Mohd Shariff, Zalilah; ,, Siti Fatimah; MN, Siti Norazlin; et al. (Persatuan Pemakanan Malaysia, 2012)
Introduction: Meal patterns have received little attention in nutrition studies. The aim of this study is to present the findings on general meal patterns of Malaysian adults. Methods: The Malaysian Adults Nutrition Survey (MANS), carried out in 2002 and 2003, involved 6,928 adults selected by stratified random sampling from all households by zone in Peninsular Malaysia, Sabah and Sarawak. Results: In general, the results showed that most respondents (74.16%) ate three meals per day; 89.20% of the respondents consumed breakfast, while 88.57% consumed lunch and 91.97% consumed dinner with no significant difference in terms of sex. In Peninsular Malaysia, the Northern Zone had the highest number of people consuming breakfast compared to other zones. Meanwhile, the population in Sarawak had the largest proportion of people consuming lunch and dinner, but the smallest proportion of people consuming breakfast. A significantly higher number of the rural population consumed breakfast and lunch than urbanites; however there was no significant difference in dinner consumption. Generally, breakfast consumption increased with age whereby significant difference existed between the 18 to 19 years age group and the age group of 30 years and older. Lunch intake among the age groups showed no significant difference. In contrast, dinner consumption was significantly lower among the 18 to 19 years age group compared to all other age groups. Comparison among the ethnic groups showed that the Indian population had the lowest percentage of having breakfast and lunch while the Orang Asli had the lowest percentage of consuming dinner. However, the Orang Asli recorded the highest percentage for taking breakfast and lunch while the Chinese had the highest percentage of taking dinner. Conclusion: Considering that Malaysian adults consumed their conventional breakfast, lunch and dinner, these findings indicatethat Malaysians are maintaining their traditional meal patterns.